Komunikasi Konseling Pada Program Dharma Wacana Dan Dharma Tula Di Dusun Ngis Kecamatan Narmada - Sayu Kadek Jelantik (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2021)
Counseling communication in the Dharma Wacana and Dharma Tula programs is an educational program for Hindus in internalizing Hindu religious teachings that are sourced from the Vedic Scriptures. Dharma discourse is one of the communication tools for Hindus in conveying Vedic teachings to direct and solve all Hindu problems so that it becomes an effective Hindu counseling communication model. This study describes the process of counseling communication in the Dharma Wacana and Dharma Tula programs in Dusun Ngis, Narmada District. This type of qualitative descriptive research uses the expose facto method. The concept of dharma wacana and dharma tula as tools for education and to Hindus in Indonesia in the form of Hindu religious speeches in the Guidance and counseling program is a personal, interpersonal, and group approach. The program of dharma wacana and dharma tula in guidance and counseling-based communication methods does not only help individuals or groups of Hindus solve life problems, but its main purpose is to change religious thought patterns and behavior and strengthen the spiritual-religious dimension of Hindus. The value messages of Hindu teachings originating from the Wedas are implemented in religious life which is conveyed in the Dharma Wacana Program based on Guidance and Counseling in Ngis Hamlet, Narmada District, which is the object of study in this study. The author found that it is not uncommon for the resource person to provide answers to the listener's questions by using the counseling communication model in the Dharma Wacana and Dharma Tula programs. The communication model referred to mainly in the use of spoken language as a communication tool with a counseling character. This is because the activities of dharma discourse in which the use of spoken language is a determinant of the effectiveness of answering a problem presented by the listener.